Oscillation and sensor properties of integrated opto-chemical sensors in different solvents - Berdybaeva, Sh. T.; Telminov, Evgenii N.; Solodova, Tatyana A.; Nikonova, Elena N. (Russian physics journal)
The paper studies the sensor properties of poly[(9,9-dioctylfluorenyl-2,7-diyl) polymer with terminal dimethylphenyl (ADS129) groups to detect the nitro compound vapor in a laser oscillation mode after the formation of the nitro compound molecular complex. Different solvents are used to obtain ADS129 films.